The extraction State : a history of natural gas in America - Blanchard, Charles (Natural gas researcher) (University of Pittsburgh Press, 2020)
The history of the United States of America is also the history of the energy sector. Natural gas provides the fuel that allows us to heat our homes in winter and cool them in summer with the touch of a button or turn of a dial--when the industry runs smoothly. From the oil crisis of the 1970s to the fall of Enron and the California electricity crisis at the turn of the century to contemporary issues of hydraulic fracking, poorly conceived government policies have sometimes left us shivering, stranded, or with significantly lighter wallets. In this expansive narrative, Charles Blanchard traces the rise of natural gas and the regulatory missteps that nearly ruined the market. Beginning in the 1880s, 'The Extraction State' explains how the New Deal regulatory compact came together in the 1920s, even before the Great Depression, and how it fell apart in the 1970s. From there, the book dissects the policies that affect us today, and explores where we might be headed in the near future.